Effect of niclosamide on the tegumental surface of Haplorchis taichui using scanning electron microscopy - K. Kumchoo (2018)
The effect of niclosamide on the tegument of adult Haplorchis taichui (Trematoda: Heterophyidae) exposed in vitro was observed by scanning electron microscope. Adult worms were incubated in Tyrode's solution containing 0.01, 0.1, 1.0, and 10 μg ml-1of niclosamide for 30 min, 1, 6, 12 and 24 h. Control groups were incubated in Tyrode's solution without niclosamide and worms remained active until 24 h. In 0.01 μg ml-1of niclosamide, worms showed slightly active movements up to 1 h after incubation, while in 0.1 μg ml-1solution a few worms showed only slightly active movements after 30 min. Tegumental changes were determined by scanning electron microscopy. Swelling and blebbing of the tegument were observed on both ventral and dorsal sides. After longer periods, extensive swelling and blebbing of the tegument became more severe and there was a loss of the apical plasma membrane in some regions. Empty spine sockets occurred, and small perforations penetrated the basal lamina, followed by some lesions. Destruction of both surfaces was more pronounced on the posterior compared with the anterior regions. © 2007 Cambridge University Press.